2019
DOI: 10.1155/2019/2138525
|View full text |Cite
|
Sign up to set email alerts
|

Credit Default of Local Public Sectors in Chinese Government‐Pay PPP Projects: Evidence from Ecological Construction

Abstract: Credit is regarded as a key factor to maintain the sustainability of cooperation between public authorities and social capitals in Government-Pay Public-Private Partnership (PPP) projects. The credit default of local public sectors has become a formidable force to cause termination in several cases. The study aims to explore the critical conditions and main logics behind opportunistic behaviours through literature analysis. In this research, political performance, fiscal illusion, subjective willingness, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 153 publications
0
5
0
Order By: Relevance
“…The "focus effect" of news reports is expectant with the huge pressure of public opinion which urges local governments to pay attention to public demand and achieve the goal of decision-making democratization [41][42][43]. Previous studies have shown that news reports play an important role in the policy diffusion of examples such as a public bicycle program [42,44], local government performance evaluation [37], and government purchase of public services [43,45] and in other fields [44,46].…”
Section: Hypothesis 6 (H6)mentioning
confidence: 99%
See 1 more Smart Citation
“…The "focus effect" of news reports is expectant with the huge pressure of public opinion which urges local governments to pay attention to public demand and achieve the goal of decision-making democratization [41][42][43]. Previous studies have shown that news reports play an important role in the policy diffusion of examples such as a public bicycle program [42,44], local government performance evaluation [37], and government purchase of public services [43,45] and in other fields [44,46].…”
Section: Hypothesis 6 (H6)mentioning
confidence: 99%
“…The current study's results are consistent with the findings of many Chinese [29,34] and foreign studies. Local governments' willingness is the basis for the implementation of innovation policies, while the pressure of public service demand arising from population size is an important driver for local governments to adopt innovation [42,44].…”
Section: Model Analysismentioning
confidence: 99%
“…In Singapore, which is widely regarded as politically stable, unstable government behavior is seen as the fifth most critical risk factor in adopting PPP projects given a long concession period (Hwang et al, 2013). The credit default of local public sectors has become a formidable force to cause termination in several cases (Yang et al, 2019). And government credit risk has seriously restricted the progress of PPP projects and hindered the sustainable development of PPP model (Ryan, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are many different forms of the government default, such as renegotiation of the contract, bailout of the private operator or even termination of the contract (Vecchi et al, 2017). Compared with other credit default behaviors, government buyback and direct termination are the most common methods (Yang et al, 2019). Therefore, the government default behaviors can be explained by model that the government buys back the program at a price…”
Section: ( ) ( )mentioning
confidence: 99%
“…From the factor analysis, it can be seen that the stakeholders of water PPP projects concur that the construction quality of a project is the critical factor affecting sustainability, which indicates that water PPP projects themselves universally have some quality problems. is is mainly attributed to the complex structure and relationships, high technical content, and luck of definite user fee PPP project, leading to opportunistic behaviors of governments or private sector [92]. In order to improve the construction quality, several measures should be taken in every phase of project lifecycle, so as to effectively improve project performance and achieve sustainable development goals.…”
Section: 22mentioning
confidence: 99%